Exploring the relationship between carbon performance, carbon reporting and firm performance: A conceptual paper - Abd Rahman, Noor Raida; Rasid, Siti Zaleha Abdul; Basiruddin, Rohaida (Elsevier Ltd., 2014)
In recent years, there has been an increased interest in carbon information disclosure.This research aims to examine carbon reporting practices of Malaysian companies.Further analysis will be conducted to examine the influence of internal organizational factors on the carbon reporting practices.The relationship between carbon performance, carbon reporting and firm performance will be investigated. This paper also explores the moderating effect of the corporate governance quality on the relationship between carbon reporting practices and firm performance.The findings from this study have a significant contribution to carbon reporting literature, Malaysian companies, government and accounting regulation body.